Pengaruh Rasio Tepung Beras dengan Tepung Labu Kuning (Cucurbita moschata durch) Terhadap Karakteristik Sumping - Mukhlis Prastianto, Muhamad; Suter, I Ketut; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPA, 2021)
The aims of this research was to determine the effect of the ratio of rice flour to pumpkin flour on sumping characteristics and to find the right ratio between the amount of rice flour and pumpkin flour to produce sumping with the best characteristics. The research design used was a completely randomized design with the treatment ratio between the amount of rice flour and pumpkin flour each as follows: 100%: 0%, 90%: 10%, 80%: 20%, 70%: 30%, 60%: 40% and 50%; 50% The treatment was repeated three times so obtained 18 experimental units and the data were analyzed by analysis of variance. If there is an influence on the measured variable, proceed with the Duncan test. The results showed that the ratio between the amount of rice flour and pumpkin flour significantly affected the water content, fat, ?-carotene, color, aroma, taste, texture and overall acceptance. The ratio of rice flour and pumpkin flour that produces sumping with the best characteristics is P5 (50%; 50%), with the following characteristics: 39.53% moisture content 2.57%, ash content 8,16%, protein content 8.16%, fat content 7,32%, carbohydrate content 45.29%, ?-carotene content 28.04%, and sensory properties namely: color, aroma, taste, texture, and overall acceptance are accepted by liking criteria.